Journalistic education: actual aspects and trends - Valkouski, Mikhail A. (Journal of the Belarusian State University. Journalism, 2019)
The article discusses the practical problem of training of journalist in the context of digitalizacije media environment and media transformation. The priorities of the formation of competencies and skills of journalists, taking into account the global context and the current demands of the media industry, a combination of new practices with experience in teaching the profession. In the professional and academic environment for a long time and widely held discussions about the nature and palette of modern special competencies, the mechanism of their formation among students of journalism. The introduction of digital technologies, as well as the transition in the higher school system to a two-level matrix, in which the basic and mass stage of higher education became a bachelor’s degree, gave a new impetus to the debate. Obviously, these transformations required a revision of educational practices, programs of mastering the technological foundations of the profession. Education in the context of changing technologies primarily involves the definition of the palette of competencies, the nature and scope of requirements for future professionals. The author compares the conceptual approaches and requirements to the training of professionals for the media sphere, analyzes different points of view on the content and transformation of journalistic education and formulates the main criteria for the competence of an international journalist, the formation of his professional and personal qualities in demand in the modern media space. Training of competent and responsible professionals to inform the society should include familiarity with modern methods of presenting information, the ability to work on existing media platforms and the willingness to quickly learn new skills of analysis of political, economic and socio-cultural processes from the standpoint of public interests. In our opinion, we need a variable approach to learning, in which the basic educational standard is rapidly changing in accordance with the requirements of the time. At the same time, the basic training of an international journalist should be maintained and strengthened, which involves mastering the methodology of searching and understanding what is happening in the country and in the world to create content, a systematic approach to analyzing facts. In parallel, the development of information delivery technologies in different formats, depending on the specifics of media platforms and social networks, should be carried out.
Keywords: universal journalist; journalistic education; competence; practice orientation